Digital diagnostics: A computer application for lymph node metastases in cervical cancer - Anton I. Kuznetsov (Digital Diagnostics, 2023)
BACKGROUND: Since 2020, staging accuracy improvements in cervical cancer (CC) revealed that major errors occur due to missed metastases to regional lymph nodes. The presence or absence of metastases seriously affects the staging of cancer and, consequently, its treatment methods, since metastases make cancer inoperable.